DETERMINANTS OF ACADEMIC ENTREPRENEURSHIP: A STRATEGIC ENTREPRENEURSHIP MODEL - Li Jisheng; Mohammad Saeed (Universitas Gunadarma, 2020)
Traditionally, universities are regarded as carrying two missions—teaching and research. Over later decades, in any case, they have been conjectured to donate more noteworthy consideration to a ‘third mission’—that of “contributing to the industry, the economy, the local region or the society. Universities have adopted academic entrepreneurship as the strategy to grow and influence the economy and society. Despite tremendous endeavours to grasp the third mission, universities still present extraordinary heterogeneity in their association and participation in academic entrepreneurship. This study aims to study academic entrepreneurship through the lens of strategic entrepreneurship while exploring the accountable factors of entrepreneurship orientation, entrepreneurship leadership, strategic management and organizational culture. This study promises that entrepreneurial orientation, entrepreneurship leadership, strategic management and organizational culture are imperative for the optimization of academic entrepreneurship. It is proposed that the right combination and availability of these variables will enable universities to bring forth a synergy to accelerate academic entrepreneurship. The implications and limitations of the study are presented.